2012
DOI: 10.1519/jsc.0b013e318245c09d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Saddle Height on Lower Limb Kinematics in Well-Trained Cyclists

Abstract: In cycling, proper saddle height is important because it contributes to the mechanical work of the lower limb joints, thus altering pedaling efficiency. The appropriate method to select optimal saddle height is still unknown. This study was conducted to compare a static (anthropometric measurements) vs. a dynamic method (2D analysis) to adjust saddle height. Therefore, an examination of the relationship between saddle height, anthropometrics, pedaling angles, and hamstring flexibility was carried out. Saddle h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 16 publications
3
56
1
1
Order By: Relevance
“…Power output produced by the cyclist is dependent upon the force applied to the pedals and velocity (i.e., cadence), which can be influenced by changes in the cyclist-bicycle complex. This is because changes in geometry, especially in seat height, affect the length at which muscles produce force, thus changing the force-length and force-velocity relationships and the joint movement amplitude 17 . Something that can be taken into consideration in relation to changes in the force-length relationship and, consequently, in the patterns of muscle activation, is that seat height changes generate variations in the knee and ankle joints 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Power output produced by the cyclist is dependent upon the force applied to the pedals and velocity (i.e., cadence), which can be influenced by changes in the cyclist-bicycle complex. This is because changes in geometry, especially in seat height, affect the length at which muscles produce force, thus changing the force-length and force-velocity relationships and the joint movement amplitude 17 . Something that can be taken into consideration in relation to changes in the force-length relationship and, consequently, in the patterns of muscle activation, is that seat height changes generate variations in the knee and ankle joints 28 .…”
Section: Discussionmentioning
confidence: 99%
“…The main alterations in geometry which appear to affect physiological and biomechanical parameters are related to changes in seat tube angle 6,7 , crank length 8 , and saddle height [9][10][11][12][13][14][15][16][17] . Studies have reported divergent results regarding changes in saddle height.…”
Section: Introductionmentioning
confidence: 99%
“…In cycling the use of video analysis to optimize the configuration of bicycle components is increasing [7,8]. However, all guidelines are based on measurements of the cyclist in static poses without information on potentially optimum joint angles from dynamic assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Given previous studies showed that knee flexion angles are larger at dynamic compared to static assessments of cyclists [7,8], a comparison between static and dynamic analyses of joint angles for optimization of bicycle components have not fully being explored. This comparison could show that a static position of cyclists (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the sport of cycling, it has been demonstrated that static measurements of lower limb kinematics did not coincide with dynamic measurements (Ferrer-Roca et al, 2012) and significant differences have been reported in knee and ankle joint angles between static and dynamic measurements (Peveler et al, 2012).…”
Section: Introductionmentioning
confidence: 99%